2021
DOI: 10.3390/polym13091385
|View full text |Cite
|
Sign up to set email alerts
|

A Tröger’s Base-Derived Covalent Organic Polymer Containing Carbazole Units as a High-Performance Supercapacitor

Abstract: Porous organic polymers have been received considerable attention due to their heteroatom-containing structures and high surface areas, which can offer high electrochemical performance in energy applications. The majority of reported Tröger’s base-functionalized porous organic polymers have been applied as effective candidates for sensing and gas separation/adsorption, while their use as electrode materials in supercapacitors is rare. Here, a novel covalent microporous organic polymer containing carbazole and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 70 publications
(92 reference statements)
0
18
0
Order By: Relevance
“…Covalent organic frameworks, covalent triazine frameworks, intrinsic microporous polymers, hyper cross-linked polymers, and conjugated microporous polymers (CMPs) are a few examples of the newly discovered polymeric families with high surface areas that have been employed in gas storage, pollutant removal adsorbents, water-splitting catalysts, sensors, and energy storage and conversion materials. [1][2][3][4][5][6][7][8][9][10][11] CMPs stand out from other porous materials due to their extended p-conjugated architectures, high surface area, extensive functionalization with various organic groups, uniform micropores, outstanding thermal and chemical resistance, and tunable physical properties. 11,12 Additionally, CMPs are synthesized using tunable building units, resulting in nanoarchitectures that can be utilized in a widespread applications including gas adsorption, catalysis, energy storage and conversion, uorescence, and chemical sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Covalent organic frameworks, covalent triazine frameworks, intrinsic microporous polymers, hyper cross-linked polymers, and conjugated microporous polymers (CMPs) are a few examples of the newly discovered polymeric families with high surface areas that have been employed in gas storage, pollutant removal adsorbents, water-splitting catalysts, sensors, and energy storage and conversion materials. [1][2][3][4][5][6][7][8][9][10][11] CMPs stand out from other porous materials due to their extended p-conjugated architectures, high surface area, extensive functionalization with various organic groups, uniform micropores, outstanding thermal and chemical resistance, and tunable physical properties. 11,12 Additionally, CMPs are synthesized using tunable building units, resulting in nanoarchitectures that can be utilized in a widespread applications including gas adsorption, catalysis, energy storage and conversion, uorescence, and chemical sensors.…”
Section: Introductionmentioning
confidence: 99%
“…SCs are categorized into electrochemical double-layer capacitors (EDLCs), pseudocapacitors, , and hybrid capacitors according to the charge–discharge mechanism. Parallel-plate and fiber-shaped SCs , can be identified according to the shape of the devices.…”
Section: Introductionmentioning
confidence: 99%
“…Porous organic polymers (POPs), including hyper-cross-linked polymers (HCPs), covalent organic frameworks (COFs), porous aromatic frameworks (PAFs), and conjugated microporous polymers (CMPs), have attracted the attention of researchers due to their high specific surface area, robust covalent bonding, flexibility, optimal stability under a variety of severe conditions, potent structural design ability, and convenience of functional modification to meet specific needs. In addition, their simplicity of modification allowed them to boost the adsorption capacity by integrating the required functional groups into their framework. , Thus, POPs with sufficient active functional sites in the narrow pore wall can be used for a number of applications, including as gas storage and detecting, Li batteries, and catalysis for the synthesis of fine compounds. Interestingly, the insertion of nucleobases that participate in hydrogen bonding into the primary skeleton of POPs significantly improves optoelectronic capabilities and broadens the applicability of polymers. , These nucleobase-functionalized synthetic polymers could also construct fascinating structures for advanced applications such as sensors, self-healing nanomaterials, adhesives, and templated arrays of nanoparticles, and they are a new idea in organic electrical devices. Furthermore, Cheng et al found that the addition of uracil units into the polymer structure greatly improves the physical connectivity of organic polymers …”
Section: Introductionmentioning
confidence: 99%